Barriers to breast-feeding in obese women: A qualitative exploration. Issue 5 (May 2015) - Keely, Alice; Lawton, Julia; Swanson, Vivien; Denison, Fiona C.
Abstract: Objective: to explore the factors that influence breast-feeding practices in obese women who had either stopped breast-feeding or were no longer exclusively breast-feeding 6–10 weeks following the birth of their babies, despite an original intention to do so for 16 weeks or longer. Specifically (i) to identify the barriers to successful breast-feeding and reasons for introducing formula and/or stopping breast-feeding, and (ii) to explore the women׳s views and experiences of current breast-feeding support services. Design: descriptive, qualitative study comprising semi-structured face-to-face interviews. Interviews were audio recorded and transcribed. The data were analysed using thematic analysis. Setting: participants recruited from one large maternity unit in Scotland and interviewed in their homes. Participants: 28 obese women at 6–10 weeks following birth. Findings: three major themes emerged from the data analysis: the impact of birth complications, a lack of privacy, and a low uptake of specialist breast-feeding support. Impact of birth complications: 19 of 28 women had given birth by caesarean section and some felt this led to feeling 'out of it' post-operatively, a delay in establishing skin-to-skin contact, and in establishing breast-feeding. Lack of privacy; several women described reluctance to breast feed in front of others, difficulties in achieving privacy, in hospital, at home and in public. Low uptake of postnatal breast-feeding support; despite experiencing problems such as physical difficulties during breast-feeding or a perception of low milk supply, breast-feeding support services were underused by this sample of women. A small number of the women in this study used breast-feeding clinics and reported finding these useful. A further small number felt they benefitted from the support of a friend who was successfully breast-feeding. Conclusion and implications for practice: midwives should be mindful of the presence of additional factors alongside maternal obesity, such as caesarean delivery, physical difficulties when breast-feeding, poor body image, and lack of confidence about sufficient milk supply. Scope for innovation within hospital policies with regard to both the facilitation of early skin-to-skin contact and privacy in postnatal accommodation could be explored in future research. Women should be provided with information about the provision and specific purpose of breast-feeding support groups and services and encouraged to access these services when appropriate. Future research could assess the usefulness of sustained breast-feeding support by health professionals, as well as partner involvement and formal peer support for this group of women. The education and training needs of health professionals in terms of supporting this group of women to breast feed may also usefully be explored. Highlights: Caesarean deliveryfrequently led to a delay in establishing skin-to-skin contact. Lack of privacy presented challenges for many women. Several women described perceiving their milk supply as insufficient. NHS breast-feeding support services were under-used in our study sample. Some women experienced physical difficulties when breast-feeding.